Pedagogic device of innovation and entrepreneurship education in Polytechnics of Zhejiang Province - Hongbo Ma; Ibnu Siswanto (Universitas Negeri Yogyakarta, 2022)
The study was aimed at describing the phenomenon and issues of IEE in polytechnics of Zhejiang province, drawing on Basil Bernstein's pedagogic device theory, and analyzing the pedagogic device of IEE from four aspects in Zhejiang. The empirical evidence was mainly gathered from the official IEE curriculum documents, government, and existing studies in the field. The purposive sampling was utilized and an SMS was sent to 14 teachers, 25 students, and 9 graduates selected for their geographical location and the ranking of polytechnics in Zhejiang province. A semi-structured interview examined how IEE cultivated their competencies. The results find out that in instructor training, Zhejiang Department of Education invests lots of resources to train many entrepreneurial mentors. In student training, polytechnics students must complete two credits of IEE courses and can apply for Start Your Business (SYB) curriculum free of charge. After seven years of development, the popularity of innovation and entrepreneurship competition has increased, and polytechnics' participation has doubled. After a decade of exploration and development, mass innovation space has evolved from the early 1.0 hardware version, which only provided sites and equipment, to the 2.0 and 3.0 software versions with capital docking and government financial policies support.